Nanomechanical behavior of hierarchical self‐assemblies of perylene bisimide derivatives. (5th January 2022) - Wang, Weijie; Yao, Qing; Sun, Abin; Wang, Wenpin
Abstract: In the field of self‐assemblies of perylene bisimide (PBI) derivatives, effect of molecular structure on the mechanical properties of assemblies is essential but still not understood in full detail. To reveal the relationships of PBI molecules and mechanical properties of their assemblies, the PeakForce Quantitative Nanomechanical Mapping (PeakForce QNM) is applied to visualize the structures and quantify the mechanical properties of assemblies formed by the model PBI derivatives (M1: C6 H13 ‐PBI‐OH; M2: C12 H25 ‐PBI‐OH). The influence of the linear alkyl chainson self‐assembly of PBI derivatives has been investigated. We found that the long‐range ordered structures could be formed for both M1 and M2 in high‐polarity solvents. M1 formed the micron‐size bricks with the Young's modulus of (3.1 ± 1.0) GPa, whereas M2 assembled into the nanosheets with the Young's modulus of (2.5 ± 0.5) GPa. The competitive, non‐competitive and cooperative interactions of the π–π stacking, hydrogen‐bond interactions, and van der Waals interactions facilitated the growth of assemblies with the different hardness and size. This method can be used to investigate the molecular self‐assembly, which helps to establish relationships among structure, performance, and corresponding application of assemblies.